Time use in out-of-class activities and its association with self-efficacy and perceived stress: data from second-year medical students in China - Song, Xinzhi (Med Educ Online, 2020)
Background: Medical students struggle with heavy workloads and face unique time management challenges, calling for insight on medical students’ time use in out-of-class activities and related psychological factors. Objectives: To investigate Chinese medical students’ time use in out-of-class activities and its association with self-efficacy and perceived stress. Design: 940 second-year medical students were invited to participate in the survey. A questionnaire was developed to investigate the amount of time participants spent on out-of-class activities. Two existing instruments were used to assess participants’ self-efficacy and perceived stress. Descriptive statistics and logistic regression were used to analyze the data. Results: 686 students (72.98%) completed the survey. On average, students spent about 14.4 hours per week (HPW) preparing for class and studying, 13.8 HPW on leisure and recreation, 4.8 HPW on physical exercise, 4.1 HPW on student clubs, 1.9 HPW on volunteering, and 1.9 HPW on part-time jobs on/off-campus. After controlling for demographic factors, higher self-efficacy was associated with more time preparing for class and studying (OR = 1.29, 95%CI: 1.10 ~ 1.52). Higher perceived stress was associated with less time preparing for class and studying (OR = 0.84, 95%CI: 0.72 ~ 0.98), exercising (OR = 0.82, 95%CI: 0.69 ~ 0.97), and volunteering (OR = 0.81, 95%CI: 0.67 ~ 0.97). Conclusions: Chinese medical students reported more time spent on preparing for class and studying and less time spent on volunteering and part-time jobs on/off-campus. Time spent preparing for class and studying was associated with higher self-efficacy and lower perceived stress, while perceived stress was also associated with less time spent on physical exercise and volunteering. Medical schools may need to employ measures to develop their students’ self-efficacy and maintain a relatively low level of perceived stress, especially in students who also have a low level of self-efficacy.